Experimental investigation on shear behavior of high-strength friction-grip bolt shear connectors in steel-precast UHPC composite structures subjected to static loading. (1st October 2021) - Fang, Zhuangcheng; Liang, Weibin; Fang, Haozhen; Jiang, Haibo; Wang, Shaodi
Highlights: Group effect can be negligible even with a bolt spacing as low as 80 mm. A thickness greater than 75 mm is suggested for precast UHPC slabs. The bolt diameter larger than 22 mm can guarantee the ductility performance. Formulas for shear capacity and the load-slip relationship of HSFGB are proposed. Abstract: Steel-precast ultra-high-performance concrete (UHPC) composite structures with high-strength friction-grip bolt (HSFGB) shear connectors offer several advantages, such as shortening the onsite construction time, making it possible to replace deteriorated components rapidly, and improving structural durability. However, there is limited investigation on steel-UHPC composite structures with HSFGB shear connectors. Addressing this issue, this study presents a systematic experimental study on shear behaviors of HSFGB shear connectors in steel-precast UHPC composite structures by conducting 18 push-out tests. The major considered parameters are the slab concrete type, bolt grade, bolt diameter, slab thickness, pretension force, and arrangement of the shear connectors. Test results demonstrated that the shear capacity and friction resistance can be enhanced with increasing in the bolt grade and bolt diameter. In addition, there was no reduction in the shear strength of each bolt as the shear connectors were arranged in a group, and even with the spacing decreased to 80 mm. Moreover, it was recommended that the HSFGB and UHPC can be optimally utilized with a 75-mm-thickness prefabricated UHPC panels. Finally, more accurate formulas were developed for predicting the shear capacity and the load-slip relationship of HSFGB shear connectors in steel-precast UHPC composite structures, which provided feasible design approaches for engineers.